2013
DOI: 10.1128/iai.00585-12
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing and Functional Annotation of Avian Pathogenic Escherichia coli Serogroup O78 Strains Reveal the Evolution of E. coli Lineages Pathogenic for Poultry via Distinct Mechanisms

Abstract: f Avian pathogenic Escherichia coli (APEC) causes respiratory and systemic disease in poultry. Sequencing of a multilocus sequence type 95 (ST95) serogroup O1 strain previously indicated that APEC resembles E. coli causing extraintestinal human diseases. We sequenced the genomes of two strains of another dominant APEC lineage (ST23 serogroup O78 strains 7122 and IMT2125) and compared them to each other and to the reannotated APEC O1 sequence. For comparison, we also sequenced a human enterotoxigenic E. coli (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
75
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 90 publications
1
75
0
1
Order By: Relevance
“…These characteristics were corroborated by multilocus sequence typing (MLST) and genome comparison data (Johnson et al 2007, Moulin-Schouleur et al 2007) and led to a further hypothesis that APEC strains could act as UPEC or NMEC and, therefore, constitute a zoonotic risk. A recent work (Dziva et al 2013) demonstrated that an APEC strain was more closely related to a human ST23 ETEC (enterotoxigenic E. coli) than to strain APEC O1. This suggests that the core genome of ST23 strains has the potential to generate variants able to cause disease on avian or human, depending of the accessory genome.…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics were corroborated by multilocus sequence typing (MLST) and genome comparison data (Johnson et al 2007, Moulin-Schouleur et al 2007) and led to a further hypothesis that APEC strains could act as UPEC or NMEC and, therefore, constitute a zoonotic risk. A recent work (Dziva et al 2013) demonstrated that an APEC strain was more closely related to a human ST23 ETEC (enterotoxigenic E. coli) than to strain APEC O1. This suggests that the core genome of ST23 strains has the potential to generate variants able to cause disease on avian or human, depending of the accessory genome.…”
Section: Introductionmentioning
confidence: 99%
“…These species include E. coli and members of the genera Shigella , Yersinia and the family Pasteurellaceae617. Studies on FusA homologues in these species are limited, however upregulation in response to iron limitation and the presence of host factors has been demonstrated24. In a recent study, the E. coli homologues of both FusA and the predicted periplasmic protease FusC were shown to be important for the fitness of the UPEC strain CFT073 in systemic infection of mice.…”
Section: Discussionmentioning
confidence: 99%
“…The gfc-encoded group 4 capsule is synthesized by various E. coli strains, as shown for enteropathogenic E. coli (EPEC) O127:H6, enterohemorrhagic E. coli (EHEC) O157:H7, and APEC O78:H9 (29,54,55). Furthermore, strains with mutation of the gfc locus in APEC O78:H9 strain X7122 are attenuated (54), while the group 4 capsule masks surface structures of EHEC O157:H7 and affects intestine colonization (55). The gfc locus is absent in UPEC strains (29).…”
Section: Discussionmentioning
confidence: 99%